M Motives For Using Reels Instagram Social Media Among Children - Lathifah Az Zuharah, Lathifah Az Zuharah; Ade Putranto Prasetyo Wijiharto Tunggali, Ade (COMMICAST, 2022)
Technology that develops from time to time makes a person more active in using social media. Cellular phone companies are also developing various services (4G, 5G, and others) to support these needs. Social media has become an integral part of everyday life among children, where they can share information or do other things for fun. This is a necessity for them. Reels Instagram is one type of social media that is currently widely used by children. This paper aims to look at the pattern of using Instagram among teenagers. This study uses a qualitative descriptive method, with five active teenagers who use Instagram as samples or informants. Data collection techniques in this study were observation, interviews and document collection in the form of photos and other files. From the results of the study it can be concluded that Instagram is a social media that is able to meet one's needs, namely cognitive, affective, personal integration, social integration and imagination needs.